Keanekaragaman Musuh Alami Tanaman Padi pada Lahan Lebak di Tiga Desa Kecamatan Sungai Pandan Kabupaten HSU - Farida Adriani; Nur Hafizah (LPPM Sekolah Tinggi Ilmu Pertanian Amuntai, 2016)
Utilization of insect diversity is useful in overcoming pest in the field, by using parasitoids and predators to control pests, can prevent the use of toxic chemicals in the field, while providing a safe haven for other species to live and play its role in maintaining the health of the ecosystem. Insect diversity in South Kalimantan, especially paddy fields in swampy areas largely unknown, and therefore need to be examined. The aim of this study is to identify and assess the diversity of natural enemies in paddy crop in swampy areas, especially in the three villages in the district of Sungai Pandan, Hulu Sungai Utara. This study was conducted from February - June 2015. The method used in this research is survey method with direct observation with an area of rice fields has been determined, and sampling arthropod natural enemies by using a swinging nets, water traps and light traps. Results from this study are: (1) The number of arthropod natural enemies found in shallow swamps is 20 species from seven orders, mid swamps and in each of the 16 species of seven orders; (2) The highest predator arthropod population in the shallow swamp area is Micraspis sp., The middle swamp is Paederus fuscipes, and the deep swamp is Micraspis sp. ; and (3) the diversity index of natural enemies of arthropods on the third mainland is low